Interventional Study Based on Prescription Errors in the Inpatient Units of a Tertiary Care Hospital in Calicut - Arumugam, Suresh; Prakash, Sneha; Azhakath, Sreerag; Abraham, Lydia; Prakashan, Lakshmi; Anaparakkal, Anusree (Indian Journal of Pharmacy Practice)
Background: Medication errors are the main contributors to adverse events in hospitalised patients. Optimization of drug therapy can be done by minimizing the prescription error thus enhancing patient’s quality of life and reducing health expense. Hence this project was proposed to identify prescription errors and thereafter reducing adverse events. Methods: A prospective clinical interventional study was conducted in a tertiary care hospital in Calicut. A total of 200 prescriptions were collected and audited during the study period. The collected prescriptions were assessed to identify prescription errors and other drug-related problems using prescription audit form. Results: Out of 200 prescriptions audited 166 (83%) prescriptions had errors. Prescription errors were classified into different types of which major error identified was Unit not mentioned (64.45%). More than half of the prescriptions had 1 to 3 errors per prescription (58.45%) and the errors increased with an increase in the number of medications. In department wise categorisation of errors, the majority were identified in the Department of General medicine. Most of the errors were accepted by the physician (90.36%) and the major intervention made was to modify the drug dose (24.69%). Drug-Drug interactions were found in 49 prescriptions of which (34.69%) was found to be major, (53.06%) moderate and (12.24%) minor interactions. Conclusion: The study concluded that clinical pharmacist involvement in patient care may identify, resolve and prevent prescription errors and drug-related problems in the hospital.
Keywords: Prescription error; Drug-drug interactions; Medication error; Clinical Pharmacist Intervention; Adverse events.